Microbial Metabolites: Critical Regulators in NAFLD - Dai, Xin; Hou, Huiqin; Zhang, Wanru; Liu, Tianyu; Li, Yun; Wang, Sinan; Wang, Bangmao; Cao, Hailong (Frontiers in Microbiology, 2020)
Nonalcoholic fatty liver disease (NAFLD) is the most common forms of chronic liver disease throughout the world. The relationship between gut microbiota and NAFLD has been extensively investigated. The gut microbiota involves in the regulation of NAFLD by participating in the fermentation of indigestible food, interacting with the intestinal mucosal immune system, influencing the intestinal barrier function and leading to signaling alteration. Meanwhile, the microbial metabolites not only affect the signal transduction pathway in the gut, but also reach the liver far away from gut. In this review, we focus on the effects of certain key microbial metabolites such as short-chain fatty acids, trimethylamine-N-oxide, bile acids, endogenous ethanol and indole in NAFLD, and also summarize several potential therapies targeting the gut-liver axis and modulation of gut microbiota metabolites including antibiotics, prebiotics, probiotics, bile acids regulation and fecal microbiota transplantation. Understanding the complex interactions between microbial metabolites and NAFLD may provide crucial insight into the pathogenesis and treatment of NAFLD.